ChemInform Abstract: Polymers and Kinetic Resolutions: The Insolubility of It All. Issue 17 (April 2016) - Clark, Robert W.; Akhani, Ravish K.; Wiskur, Sheryl L.
Abstract: Review: [methods for the chromatography‐free separation of enantiomers through the use of polymers in kinetic resolutions; 34 refs.